Detection of Power Transformer Disk Space Variation and Core Deformation using Frequency Response Analysis - Hashemnia, Seyednaser; Abu-Siada, Ahmed; Islam, Syed (CMD 2014, 2014)
Frequency response analysis (FRA) has become a widely accepted tool to detect power transformer winding deformation due to the development of FRA test equipment. Because FRA relies on graphical analysis, interpretation of its signature is a very specialized area that calls for skilled personnel, as so far, there is no reliable standard code for FRA signature classification and quantification. Many researchers investigated the impact of various mechanical winding deformations on the transformer FRA signature by changing particular electrical parameters of the transformer equivalent electrical circuit. None of them however, investigated the impact of physical fault levels on the transformer FRA signature as it is very difficult to implement faults within real transformer without damaging it. In this paper, the physical geometrical dimension of a power transformer is simulated using 3D finite element analysis to emulate the real transformer operation. Physical core deformation and disk space variation are simulated and the impact of each fault on the transformer FRA signature is investigated.